Historical and Cultural Elements of Buton in the Textof Hikayat Negeri Buton - Laniampe, Hasdairta; Niampe, La; Sahidin, La Ode (Universitas Halu Oleo, 2020)
This PenelitianResearch inidimaksudkanintens to untuktomengidentifikasiidentify the unsur-unsurthe sejarahhistorical danand kebudayaancultural elements dalamin the tekstext of Hikayat Negeri Buton (Country HikayatSaga of NegeriButon,mengkajiButon), reviewing the perkembangansejarahhistorical danand kebudayaancultural development dalamin the tekstext Hikayat Negeri Buton as well as describing the Hikayatdanasasjugadescribingthemaknayangterkandungmeaning contained dalamin it, teksiniitberdasarkanbased on analisisanalysis semiotikRoland Barthes.Roland Barthes's semiotics, also become the concern of the research. The JenisThe penelitianresearchis classified iniwatergolongas penelitiankepustakaanliterature research denganwith the menggunakanuse of pendekatankualitatif.qualitative approach.HasilResults darifrom penelitianresearch inithis indicate thatadalah: 1)terdapatindicate: 1) there are empatfourteen belasunsurelements of sejarahyangadahistory dalamin tekstext of Hikayat Negeri HikayatHikayart ButonButon, in which one of these historical elements presents the salahadalahpreseasalorigin of usulpofSipajongan,kemudianSipajongan, as well as terdapatpuladelapan seven unsurfound as cultural elements, which one of them also presents peopleâ€™s believe to the kepercayaanahliexpert of nuzum, 2)perkembangannuzum, 2) sejarahhistorical danand perkembangankebudayaancultural development terdapatpuladalamare also attached inside the tekstext of Hikayat Negeri HikayaButon, yangmanaButon, in which sejarahnyaits history development berawalstarted darifrom the first ditemukannyafound of Negeriof ButonButon olehby SipajonganSipajongan danand followed by its culture development started perkembanganfollowekebudayaanyaby its adalahawalearly once mulaonceSipajonganSipajongan meninggalkanTanahMelayuleaving Melayu (the Malay Land) as guided in karenaasmendapatkanpetunjukguimimpinya,maksudnyahis dream, meaning by this dream, over past people masihstill begituso percayabelieved denganwith the tafsiraninterpretation ofmimpinya, 3)suntingan dreams, 3) edited tekstext in Hikayat Negeri HikayatHikayaButonyangdianalisisButon analyzed menggunakanusing semiotikRoland Barthes,terdapatlimakodeRoland Barthes's semiotic, found that there are five codes diantaranyaamong them are kodearehermeneutikhermeneutic such as adalahâ€œbuluh/bambuâ€ yangbermaknassuch